General Election Commission Public Communication Strategy in Increasing General Election Participation in Blitar - Tiara Lora Amida; Sintar Nababan; Widhihatmini; Ardian Setio Utomo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The Blitar City General Election Commission (KPU) in the 2019 election succeeded in achieving the target number of public participations of 84% compared to 78% in the 2014 election. The KPU's success in increasing public participation in the 2019 election certainly had a good communication strategy. This research aims to determine the KPU's public communication strategy in increasing participation in the 2019 election in Blitar City. This research uses a qualitative approach with data collection techniques in the form of interviews, observation, and documentation. This research uses Lasswell's communication strategy theory, namely selecting and determining communicators, determining target audiences, using techniques for composing messages and choosing media or communication channels. The research results show that the KPU's strategy in determining communicators involves all KPU members and staff, coordinates with relevant stakeholders, and forms ad hoc bodies and Democracy Volunteers. The KPU's strategy in preparing messages is to use language adapted to the target audience, namely local and contemporary languages. The KPU's strategy in choosing media or communication channels uses online, offline, and communication channels. This strategy has succeeded in increasing community participation in accepting political stimuli, individual social characteristics, political systems, political parties, and regional differences so that socialization can be accepted and understood effectively.